2002
DOI: 10.1159/000068795
|View full text |Cite
|
Sign up to set email alerts
|

Skin Paints (Pseudo-Tattoos) with ‘Black Henna’: Hazards and Long-Term Risks

Abstract: Background: Skin paints, traditionally performed with henna, are sometimes realized with hair-dyeing preparations like ‘black henna’ containing aromatic amines. Observations: Nine patients, 7 women and 2 men aged 9–41 years, had had skin painting with ‘black henna’. Six experienced acute manifestations: flare-up (1), eczema (1) or both (1), eczema after hair dyeing (1) or chemical burn (2). Two were symptom free. In 1, a positive p-phenylenediamine (PPD) patch test was explained by previous pseudo-tattooing. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…A recent study from Copenhagen showed that one fifth of purchased items released nickel in concentrations that may lead to nickel allergy (20). Although PPD may not be the actual sensitizer in all cases of hair dye allergy, it is a marker for other diaminobenzenes used in hair dyes (21). Of the 23 patients positive for toluene‐2,5‐diamine, 83% ( n = 19) also tested positive for PPD.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from Copenhagen showed that one fifth of purchased items released nickel in concentrations that may lead to nickel allergy (20). Although PPD may not be the actual sensitizer in all cases of hair dye allergy, it is a marker for other diaminobenzenes used in hair dyes (21). Of the 23 patients positive for toluene‐2,5‐diamine, 83% ( n = 19) also tested positive for PPD.…”
Section: Discussionmentioning
confidence: 99%